1909 Osmanlı Kanuni Esasi tadilleri çerçevesinde kanun yapma usulü - Mengüç, Yaşar Fatih (My University, 2014)
1876 Kanun-i Esasi, Türk İslam siyasi tarihinde ilk yazılı anayasa olarak kabul edilmekte olup, Osmanlı Devleti özelinde bir parlamentonun gündeme gelişi ve rejimin mutlakıyetten meşruti monarşiye dönmesi itibarı ile de, oldukça önemli ve tarihsel bir dönüm noktasına referans vermektedir. Özellikle, eş zamanlı olarak Batı'da gelişen anayasacılık hareketlerinin, Osmanlı aydınlarının (Genç Osmanlılar; Midhat Paşa, Ziya Paşa, Namık Kemal vb.) ve bürokrasinin, fikir dünyasına olan etkileri sonucu Sultan II. Abdülhamid, Kanun-i Esasi'yi ilan edeceği sözü ile tahta gelmiş ve 1876'da Kanun-i Esasi ferman hüviyetinde ilan edilmiştir. Ancak iki yıl yürürlükte kalan Kanun-i Esasi, yürürlükten kaldırılmasa da, Osmanlı-Rus savaşı (1878) nedeniyle askıya alınmış ve parlamento da tatil edilmiştir. 1908 yılında, Genç Osmanlılar'ın devamı olan Jön Türkler'in, örgütleşmiş hali diyebileceğimiz İttihadçılar, gerek dış konjonktür gerekse de ülkenin sorunlarına Kanun-i Esasi'nin yeniden ilanının çözüm olacağı inancıyla, Sultan II. Abdülhamid'i zorlamışlar ve 30 yıl sonra 1908'de Kanun-i Esasi'yi yeniden ilan ettirmişlerdir. 31 Mart Vakası olarak anılan olay sonrasında, Sultan Abdülhamid'i tahttan indiren İttihadçılar, 1909 Kanun-i Esasi Tadilleri ile anayasayı, yasamanın lehine tadil etmişlerdir. Bu aynı zamanda kanun yapma usulünün (tekniğinin) yasamanın ağırlığında olduğu bir döneme referansıdır. Klasik Dönem, Anayasal Devlet, Anayasalı Devlet, II. Abdülhamid, Kanun-i Esasi, 1909 Tadilleri

1876 Constituion is considered to be the first written constitution in Turkish-Islamic political history why it refers that a historical turning point due to parliament's existence in the case of the Ottoman Empire and the advent of the agenda of the regime which effect from absolutism to return constitutional monarchy. In particular, due to the results of the effects of the constitutional movements which were developed in the West on intelectuals of Ottomans (the Young Ottomans; Mithat Pasha, Ziya Pasha, Namık Kemal and so on) and world of ideas of Ottoman bureaucracy, Sultan II. Abdulhamid said the board would declare Constitution have been announced and is characterized as a Sultan decree. Although, Constitution was in current, it was repealed after two years due to Ottoman- Russian War (1878) and parliament was closed. Ittihad and Terakki which were organized form of Young Turks who were maintainers of political tradition based on the Young Ottomans, forced II. Abdulhamid to has been anounced Constitution again and made him that after 30 years, in 1908, both external conjucture of the country as well as the belief that the solution to the problems of declaration of Constitution. Ittihad and Terakki dethroned II. Abdulhamid after the event known as the March 31 Incident and they restored the Constitution as in favor of the legislative with the 1909 Restorations. It also refers that the term when law-making procedure was dominated by legislature. Classical Period, Constitutional Government, Constitutional State, II. Abdulhamid, 1876 Constitution, 1909 Restorations
Keywords: 1909 Tadilleri; Anayasa; Anayasal Devlet; II. Abdülhamid; İslam Tarihi; İttihatçılar; Kanun-i Esasi; Türk Hukuk Tarihi